SEC‐SAXS and HDX‐MS: A powerful combination. The case of the calcium‐binding domain of a bacterial toxin. (2nd October 2017) - O'Brien, Darragh P.; Brier, Sébastien; Ladant, Daniel; Durand, Dominique; Chenal, Alexandre; Vachette, Patrice
Abstract: Small‐angle X‐ray scattering (SAXS) is a relatively simple experimental technique that provides information on the global conformation of macromolecules in solution, be they fully structured, partially, or extensively unfolded. Size exclusion chromatography in line with a SAXS measuring cell considerably improves the monodispersity and ideality of solutions, the two main requirements of a "good" SAXS sample. Hydrogen/deuterium exchange monitored by mass spectrometry (HDX‐MS) offers a wealth of information regarding the solvent accessibility at the local (peptide) level. It constitutes a sensitive probe of local flexibility and, more generally, of structural dynamics. The combination of both approaches presented here is very powerful, as illustrated by the case of RD, a calcium‐binding protein that is part of a bacterial virulence factor.